The Motivation to Volunteer and Change of Attitudes Towards Volunteering in a Post-Soviet Country - Pranaitytė, Irma (Social Welfare: Interdisciplinary Approach, 2024)
The paper explores the attitudes towards volunteering and the change of attitudes towards volunteering in a Post-Soviet country after the collapse of the Soviet regime. The aim of the paper is to reveal what are the factors which keep individuals away from joining voluntary organizations, how the attitude towards volunteering has been changing over 30 years and what motivates individuals to get involved in voluntary organizations. A qualitative research method has been chosen – 60 interviews with individuals who have been born in 1945–1965 and have been living under the Soviet regime. The results reveal the change of attitudes towards volunteering in five periods and how the understanding about volunteering has been changing. Voluntary organizations can use the results of the research for the attraction of potential volunteers to volunteering.
Keywords: Motivation; volunteering; compulsory volunteering; motivation to volunteer; attitudes towards volunteering